PEMANFAATAN MANGROVE (SONNERATIA CASEOLARIS) DAN NIPAH(NYPA FRUTICANS) UNTUK MINUMAN KESEHATAN - Widia Dara; Advenrinus Majus Sikaraja (EcoNews, 2018)
Pidada plant is a kind of tree inhabitants of rivers swamp, and part of mangrove vegetation. Pidada fruit has the advantage that the nature of the fruit is not toxic.Nipah is a kind of palm that grows in many regions of Indonesia swamp. The aim of this research was to know the organoleptic quality and the analysis of vitamin C content and physico- chemical properties of mangrove fruit (Sonnetaria Caseolaris) added nipah (Nypa Fruticans). The research is experimental by using Completely Randomized Design (RAL) which consists of 3 treatments and 2 repetitions. Time and place of research was conducted in February - June 2017 at Food Laboratory of STIKES Perintis Padang and Physico- chemical beverage at Laboratory of Kopertis Region X and laboratory of UNAND. The analysis of organoleptic test by analyzed variance (ANOVA) at 5% level and if F count bigger than F table continued with Duncan New Multiple Test (DNMRT) test at 5% . Treatment in beverage making is done by adding nipah fruit to pidada mangrove fruit with comparison A (pidada 100%), B (nipah 100%) and C (pidada 50%: nipah 100%). Measurement of pH by means of pH meter. The sugar content is measured by hand refractometer, total acid beverage by titration method. The results organoleptic quality on color, aroma, and taste of panelist favored in treatment B. that was : nipah fruit 100%. Vitamin C content of pidada 100% drinks = 26 mg, nipah 100% driks = 88 mg and pidada 50% : nipah 50% drinks = 40 mg. Sugar content pidada drinks 100% 29,6 Brix, Drink of nipah 100% is 29.0 Brix and drinks pidada and nipah each 50% is 23 Brix. The consecutive beverage pH levels of Drink A, B and C were 3.75 and 4,04 and 3,77. Total dissolved solids of Beverage A was 19.63%, B was18.24% and C was 15.58%. The total acid of drink A 0,0048 beverage B was 0,0029 and drink C was 0.004. It is recommended to know how long the shelf life of the drink is still feasible for consumption.